Investigation of influence on critical process parameters in roller compaction process on physical properties of granules and tablets using design of experiments - Atanaskova, Elizabeta; Kostovski, Dejan; Anevska-Stojanovska, Natasa (Archives of Pharmacy, 2020)
Different granulation methods are used in the pharmaceutical industry, mainly divided as wet or dry granulation. Although roller compaction is a widely used dry granulation process, evaluation of critical process parameters has proven challenging because of the complex interactions among each individual parameter. The result of the process of roller compaction are ribbons with different properties based on the variation of the input parameters. The properties of the final product are directly related to process parameters used during dry granulation. Understanding the interaction between the roller compaction parameters will allow accurate control of the process. The aim of this study is to present the applicability of design of experiments (DoE) approach in the development of the roller compaction process. For this purpose, two level full factorial design was used to evaluate the influence of process parameters as roll pressure and speed, vertical feed screw speed and mill speed on the intermediate and final product physical properties. The results revealed that roll speed is the variable having the most impact on the granules density. The granules particle size is mostly dependent of variation in roll pressure, roll speed and mill speed. Increasing of the milling speed will create more uniform particles in aspect of span distribution. After the process of compression of granules into tablets and assessing the data, roll speed was identified as the most influencing factor regarding tablet hardness.